OP0008 Conventional radiotherapy versus altered fractionation for patients receiving radical radiotherapy for oral cancer: A randomised phase 2b trial. (July 2015) - Kainickal, C.T.; George, P.; Kumar, R.R.; Rafi, M.; Sudha, A.S.; Raghavan, R.; Ramadas, K.
Abstract : Background: Radical radiotherapy with 66–70 Gy in 33–35 fractions is the standard radiotherapy schedule in head and neck squamous cell carcinoma. Altered fractionation improves the therapeutic ratio compared to conventional radiotherapy. We did a phase 2b randomised trial to compare two radiotherapy schedules in patients undergoing radical radiotherapy in oral cancer. Methods: This study was conducted in Thiruvananthapuram, India, from May 2013 to December 2014. 76 patients with squamous cell carcinoma of oral cavity intended to be treated with radical radiotherapy were randomised either to receive conventional radiotherapy (70 Gy in 35 fractions) or altered fractionation (52.5 Gy in 15 fractions). The primary endpoints were acute toxicity and response rate. Acute toxicity was evaluated weekly during treatment using RTOG toxicity criteria. Findings: 38 patients were randomly assigned to each group. Two patients from the conventional group and four patients from the altered fractionation group were excluded from final analysis. Acute grade 2 skin toxicity was significantly more common in the conventional radiotherapy group than in the altered fractionation group (80.5% versus 2.9%; p = 0.0001). World Health Organisation (WHO) step III analgesics usage was significantly higher in the conventional group than in the altered fractionation group (52.7% versus 14.7%; p = 0.004). Complete response at 6 months was more common in the altered fractionation group than in the conventional group (91% versus 63.8%; p = 0.01). One-year disease free survival was higher in the altered fractionation group than in the conventional group (76.9% versus 54.7%; p = 0.0107). Overall survival data are pending. Interpretation: Results favoured altered fractionation radiotherapy. Longer follow-up is needed to assess late toxicity and overall survival. A phase 3 trial is warranted.